Sejarah Situs Makam Ginde Dukun - Riska Dui, Richi; Marselia Anggraini; Dewi Puspita; Agus Susilo (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to explore information to understand the history of the Ginde Dukun Tomb Site located in Batu Urip Hamlet, Lubuklinggau City. This study uses a qualitative approach using historical and ethnographic methods, with data collection techniques through in-depth interviews, direct observation and documentation. The main information was obtained from three key informants, Mr. Basir, Mr. Zulhijjah, and Mr. Sahwan Mat Lani who are customary leaders, descendants and community leaders of Batu Urip Hamlet, Lubuklinggau City. The results of this study indicate that this Ginde Dukun is a leader or position of village head (hamlet), and he is highly respected because of his position as a Ginde and someone who can help cure people or communities who are sick, because this is why he is called a shaman. So he is called a Ginde because of his position and a shaman because he is able to cure sick people. His grave site is still maintained until now even though there are no special cleaners, but when people make pilgrimages, they are the ones who help clean it. Keywords: Ginde Shaman, Grave Site, Local History.